(untitled) (Islas, 2022)
Introduction: The article identifies the presence of choral practice in the center of higher education. In Cuba, the choral movement played an important role with the birth of the amateur artists’ movement. The consolidation of a choral group at the Universidad Central «Marta Abreu» de Las Villas was not possible until the 21.st century, when the Coral Universitaria Allvento was created. Methods: The study is a historical research since it deals with past events linked to the creation and development of university choral groups. The method of reasoning by induction or Bayesian inference was applied as a specific tool of the statistical-mathematical method. The techniques used were structured and semi-structured interviews, questionnaire, triangulation of information and percentage analysis. Results: The choral practice has been linked to the Universidad Central «Marta Abreu» de Las Villas since its foundation. Several groups have performed at the institution or were created within it. Conclusions: The Universidad Central «Marta Abreu» de Las Villas was closely linked to choral practice. The existence of three choirs of ephemeral duration and the multiple attempts to create a choral group are evident. With the foundation of the Allvento choral group, the amateur choral music movement was consolidated within the university.